2019
DOI: 10.29252/jmis.5.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Challenges of Pre-Hospital Emergency Services Information System with a Systemic Approach: Case Study from the South of Iran

Abstract: Aim: Pre-hospital Emergency Medical Services (EMS) is a vital part of the health system, which given the emergency nature of its services, is an information-sensitive area. But most information systems have challenges in providing this information. This study examines the challenges of a pre-hospital emergency information system (EMSIS) with a systematic approach. Methods: In this descriptive applied study, the challenges of the EMSIS of Hormozgan EMS Management Center were investigated and extracted using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…This is because the information system in EMS leads to the integration of the system and better provision of emergency care (49). However, the current study confirms the results of the Mastaneh Mouseli study that most EMS information systems have challenges in providing this information (50). Studies indicated the existence of this challenge in Iran, even before the prevalence of corona.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is because the information system in EMS leads to the integration of the system and better provision of emergency care (49). However, the current study confirms the results of the Mastaneh Mouseli study that most EMS information systems have challenges in providing this information (50). Studies indicated the existence of this challenge in Iran, even before the prevalence of corona.…”
Section: Discussionsupporting
confidence: 89%
“…Studies indicated the existence of this challenge in Iran, even before the prevalence of corona. Challenges such as weakness in providing information system, manual registration of information, registration in isolation and nonsharing of information for EMS have been mentioned (50); in the corona situation, these challenges showed themselves more and created problems in providing services. Therefore, using electronic systems and simultaneously providing information and sending information to EMS databases, and providing hardware and software equipment for this purpose are among the solutions in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Limited access to continuing education: While there have been improvements in pre-hospital EMS education in Iran, access to continuing education and training opportunities can still be limited in some areas [ 36 , 49 , 50 , 51 ]. Inadequate compensation: Pre-hospital EMS personnel in Iran may not be adequately compensated for their work, which can lead to low morale and high turnover rates [ 3 , 52 , 53 ]. Safety concerns: Pre-hospital EMS personnel in Iran may face safety concerns due to the nature of their work, including exposure to infectious diseases, physical violence, and traffic accidents [ 48 , 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Safety concerns: Pre-hospital EMS personnel in Iran may face safety concerns due to the nature of their work, including exposure to infectious diseases, physical violence, and traffic accidents [ 48 , 50 , 52 ]. Language barriers: In some areas of Iran, pre-hospital EMS personnel may face language barriers when communicating with patients and their families, which can make it difficult to provide appropriate care [ 49 , 50 , 53 ]. Cultural and social norms: Cultural and social norms in Iran can also pose challenges for pre-hospital EMS personnel, particularly when it comes to providing care to women and addressing sensitive medical issues [ 40 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these challenges affect their quality of work in health threatening situations and the areas covered by them. 14 With the outbreak of coronavirus disease 2019 (COVID-19) epidemic, the workload of the PHES has also increased so that according to the head of Iranian emergency unit, the number of calls with emergency communication unit has increased 4-fold. 15 During the epidemic, in addition to its usual duties, the PHES is responsible for not only transferring COVID-19 positive patients between medical centers but also transferring suspected patients with COVID-19 symptoms.…”
mentioning
confidence: 99%